Lipase elevation and type 1 diabetes mellitus related to immune checkpoint inhibitor therapy – A multicentre study of 90 patients from the German Dermatooncology Group - Grimmelmann, Imke; Momma, Michael; Zimmer, Lisa; Hassel, Jessica C.; Heinzerling, Lucie; Pföhler, Claudia; Loquai, Carmen; Ruini, Cristel; Utikal, Jochen; Thoms, Kai-Martin; Kähler, Katharina C.; Eigentler, Thomas; et al. (European journal of cancer (1990), 2021)
Immune checkpoint inhibition (ICI) triggers immune-related adverse events (irAEs). The relevance of lipase elevation remains unclear. Skin cancer patients with newly detected serum lipase elevation (at least twofold upper normal limit) or newly diagnosed type I diabetes mellitus upon ICI therapy were retrospectively collected at 14 German skin cancer centres. We identified 68 patients with lipase elevation occurring after a median time of 19 (range 1–181) weeks on ICI, 15 (22%) thereof had symptoms consistent with pancreatitis. Forty-seven patients (73%) had other irAE, mainly colitis. Discontinuation (n = 24, 35%) or interruption (n = 26, 38%) of ICI resulted in decrease of lipase after reinduction of ICI lipase levels increased again in 12 of 24 patients. In 18 patients (27%), ICI was continued unchanged, and in 12 (67%) of them, lipase levels normalised. Twenty-two patients were identified with newly diagnosed type I diabetes mellitus related to ICI, and 12 (55%) thereof had also lipase elevation mainly shortly before or after the diagnosis of diabetes. Fourteen (64%) patients had other irAE, mainly thyroiditis. Irrespective of lipase elevation, patients frequently showed a rapid onset with ketoacidosis, decreased c-peptide, and strongly increased blood glucose levels. Increased serum lipase during ICI is often not associated with pancreatitis but with other irAE as possible cause. Therefore, it might be sufficient to regularly monitor blood glucose levels and perform further workup only in case of signs or symptoms of pancreatitis and/or exocrine pancreas insufficiency. •Lipase elevation is often associated with e.g. colitis but not pancreatitis.•Immune checkpoint inhibition diabetes occurs often with endocrine immune-related adverse event and in 50% with lipase elevation.•Lipase elevation shortly precedes the onset of type I diabetes mellitus.•Therefore, blood glucose but not lipase monitoring is recommended.